THE CONCEPT OF MODERN ARCHITECTURAL HEITAGE: DEFINITON AND CONTENT - Omay Polat, Elvan Ebru; Can, Cengiz (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2008)
Modern architecture has a new identity as being part of cultural heritage at the end of the 20th century. The acceptance of modern architecture as cultural heritage and the discussions on its definition and content is important in terms of pointing at the significance of conservation theory.'s dynamic character. The existing heritage and values are reevaluated with the quality and quantity of the definition and content of modern architectural heritage. The definition and content of Turkey's modern heritage should not only be discussed in terms of the changes in the international conservation field but also in the context of its own conditions.
Keywords: Conservation theory; modern architectural heritage; 20th century architectural heritage; Architecture